105k views
3 votes
Why does square root 36 equals +6 and -6.

User Toolkit
by
5.3k points

2 Answers

3 votes

Answer A negitive number times a negitive number will give you a positive number.

Explanation:

-6 multiplied by -6= 36

6 multiplied by 6= 36

User Jiri Vlasimsky
by
4.9k points
4 votes

Answer: See below

Explanation:

To find the square root of a number is the same as squaring the answer.

In this perticular example, the square root of 35 is +6 and -6.

As I said before, the square root of a number is the same as squaring the answer. That means, we square +6 and -6.

(6)²=36

(-6)²=36

It is clear that when you square 6 and -6, you get 36. This is because a positive×positive=positive, and negative×negative=positive.

That's why square root 36 equals +6 and -6.

User Shivam Anand
by
4.9k points